Comparative Outcomes of Septal Extension versus Columellar Strut Grafts for Nasal Tip Stabilization and Positioning in Rhinoplasty: A Systematic Review and Meta-analysis - Ozgenc, Ismail; Alzoubi, Dana; Vankayalapati, Dilip K.; Bayan, Laith Ali; Lee, Sum-Yu Christina; Huynh, Kelson; Waqasi, Annah; Nakanishi, Hayato; Navaratnam, Annakan V. (Facial Plastic Surgery, 2025)
Columellar strut graft (CSG) and septal extension graft (SEG) are commonly used in septorhinoplasty for nasal tip support.We aimed to systematically review and compare CSG and SEG in achieving a desired nasolabial angle (NLA) and Goode's ratio (GR).Several databases were systematically searched from inception to August 2024. A two-arm meta-analysis of the pooled means was conducted with a random-effects model. This review was registered in PROSPERO (CRD42024574909).Eligible studies included primary septorhinoplasty patients (≥17 years) receiving CSG or SEG.Eight studies met eligibility criteria including 256 CSG and 371 SEG patients. Intergroup comparison of long-term postoperative NLA favored SEG (p < 0.05) while GR showed no differences. However, SEG patients had significant improvement in GR postoperatively (p < 0.05), unlike CSG patients.SEG may provide superior long-term nasal tip rotation and projection stability.
Keywords: rhinoplasty; septal extension graft; meta-analysis; columellar strut; septorhinoplasty